To Salama’ Sheikh Muhammad Idris Ulama from Mandar - Amirullah, Amirullah (Journal of Noesantara Islamic Studies, 2024)
This research discusses To Salama’ Sheikh Muhammad Idris, who is a figure close to God who comes from Mandar. This research uses a qualitative approach. In collecting the data used is library research with various literature related to what is being studied and various other supporting data. The results of this research show that To Salama’ Sheikh Muhammad Idris is a figure who is close to God. This is proven by his frequent communication with the public even though he has been dead for a long time. This is the beginning of the large number of pilgrims who come to his grave. It is hoped that this thesis can be a lesson for the next generation that making a pilgrimage to the To Salama’ grave is a form of belief that after this worldly life there will be an afterlife and can increase our spiritual knowledge and be able to apply it in life as taught by Rasullah Saw.